Mapping the Landscape of Ethnomathematics in Mathematics Education: Trends, Pedagogical Designs, and Future Directions - Rahmawati, Dessy; Nusantara, Duano Sapta; Rohati, Rohati (Jurnal Pendidikan Matematika, 2026)
Ethnomathematics has emerged as a culturally responsive approach to mathematics education, yet its research landscape remains fragmented across geographical, methodological, and thematic dimensions. This study aims to comprehensively map the landscape of ethnomathematics in mathematics education by tracing publication trends, analyzing pedagogical designs, and identifying critical research gaps. A Systematic Literature Review (SLR) was conducted using the PRISMA framework, integrating bibliometric analysis with VOSViewer and qualitative content analysis. Of 663 Scopus-indexed articles published between 2015 and 2025, 13 articles met the inclusion criteria and were selected for in-depth analysis. Findings revealed a significant growth in ethnomathematics publications, particularly after 2023, with the most productive year being 2025. Research focus has shifted from STEAM education and game-based learning toward mathematical literacy, numeracy, critical thinking, problem-solving, and ethno-modeling. Content analysis identified three main categories of cultural artifacts employed in instructional designs: traditional architecture, agricultural and calendrical systems, and artistic and craft traditions. However, four critical gaps were identified: (1) the dominance of qualitative methods with a scarcity of experimental and longitudinal studies; (2) minimal integration of emerging technologies such as VR, AR, and AI; (3) strong geographical concentration in Indonesia with limited cross-cultural representation; and (4) insufficient research on teacher professional development and culturally responsive assessment. Future research is recommended to diversify methodological designs, develop digital ethnomathematics platforms, strengthen international collaboration, and address teacher preparation and curriculum integration systematically. This study contributes a structured research roadmap that supports the development of culturally sensitive mathematics education globally. Etnomatematika telah berkembang menjadi pendekatan responsif budaya dalam pendidikan matematika, namun lanskap penelitiannya masih terfragmentasi secara geografis, metodologis, dan tematik. Penelitian ini bertujuan untuk memetakan secara komprehensif lanskap etnomatematika dalam pendidikan matematika dengan menelusuri tren publikasi, menganalisis desain pedagogis, serta mengidentifikasi kesenjangan penelitian yang masih kritis. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan kerangka PRISMA, mengintegrasikan analisis bibliometrik menggunakan VOSViewer dan analisis konten kualitatif. Dari 663 artikel terindeks Scopus yang diterbitkan antara 2015 hingga 2025, sebanyak 13 artikel memenuhi kriteria inklusi dan dipilih untuk dianalisis secara mendalam. Temuan menunjukkan pertumbuhan signifikan publikasi etnomatematika, terutama setelah 2023, dengan tahun paling produktif adalah 2025. Fokus penelitian telah bergeser dari pendidikan STEAM dan pembelajaran berbasis permainan menuju literasi matematika, numerasi, berpikir kritis, pemecahan masalah, dan etomodeling. Analisis konten mengidentifikasi tiga kategori utama artefak budaya yang digunakan dalam desain pembelajaran: arsitektur tradisional, sistem pertanian dan penanggalan, serta tradisi seni dan kerajinan. Namun, empat kesenjangan kritis ditemukan: (1) dominasi metode kualitatif dengan minimnya studi eksperimental dan longitudinal; (2) terbatasnya integrasi teknologi seperti VR, AR, dan AI; (3) konsentrasi geografis yang kuat di Indonesia dengan representasi lintas budaya yang terbatas; dan (4) minimnya penelitian tentang pengembangan profesional guru dan asesmen responsif budaya. Penelitian selanjutnya direkomendasikan untuk mendiversifikasi desain metodologis, mengembangkan platform etnomatematika digital, memperkuat kolaborasi internasional, serta menangani persiapan guru dan integrasi kurikulum secara sistematis. Penelitian ini berkontribusi pada penyusunan peta jalan penelitian terstruktur yang mendukung pengembangan pendidikan matematika yang sensitif budaya secara global.